Liver Research and Clinical Management - Rodrigo, Luis (IntechOpen, 2018)
Hepatology is the medical specialty that studies the normal functioning of the liver and its diseases. It has experienced a steady progress in recent decades, as well as occurred in other medical specialties. It deals with the acute and chronic inflammatory processes of the liver, among which is the viral hepatitis. Recently, very effective drugs have been introduced in this field that achieves the elimination of the hepatitis C virus in the great majority of patients. Nonalcoholic steatohepatitis has increased markedly worldwide especially in Western countries in relation to overweight, diabetes, and other metabolic conditions. Cirrhosis and its complications are better managed, and patients live longer, thanks also to the earlier detection of hepatocarcinoma and the generalization of the use of liver transplants. This book deals with all of these interesting topics, thanks to the excellent collaboration of a great group of specialists that have collaborated with their knowledge and expertise in this edition.